ANALISIS PERLAKUAN AKUNTANSI ASET TETAP PADA RUMAH SAKIT SRIWIJAYA EYE CENTRE PALEMBANG - Siti Maryana Fatrianisa; Rina Tjandrakirana; Yulia Saftiana (AKUNTABILITAS, 2013)
This research aims to determine the accounting treatment of fixed assets in the Hospital Sriwijaya Eye Centre in which the company is engaged in the healthcare field. And to determine whether the accounting treatment of fixed assets of the company in accordance with generally accepted accounting treatment so as to provide future benefits to the company. Hospital Sriwijaya Eye Centre in general get their fixed assets in two ways: credit purchases, and assemble or build own fixed assets. The method used to calculate depreciation is the straight-line method for all assets except land. The results of the analysis and research conducted at the Hospital Sriwijaya Eye Centre that plant and equipment and depreciation methods used in principle has been implemented consistently and do not deviate from accounting standards generally accepted. But in this case the adjustment between the economic utilization of assets with depreciation methods applied by the company so that there are not appropriate assets that still need to be adjusted using the depreciation method to be able to provide future benefits to the company.